Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsinfecdis.7b00236
|View full text |Cite
|
Sign up to set email alerts
|

Mining a Kröhnke Pyridine Library for Anti-Arenavirus Activity

Abstract: Several arenaviruses cause hemorrhagic fever (HF) disease in humans and represent important public health problems in their endemic regions. In addition, evidence indicates that the worldwide-distributed prototypic arenavirus lymphocytic choriomeningitis virus is a neglected human pathogen of clinical significance. There are no licensed arenavirus vaccines, and current antiarenavirus therapy is limited to an off-label use of ribavirin that is only partially effective. Therefore, there is an unmet need for nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…These include the replacement of wild-type viral GPC or NP segments with eGFP (104,106,107,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124), teal fluorescent protein (125), mCherry (126,127), or ZsGreen (128)(129)(130). Not only do these reporters allow for assessment of viral replication in less time than is needed for traditional plaque assays, but also they have been a powerful tool in highthroughput screening approaches used to identify small-molecule antivirals (131), identification of receptors required for host cell infection (126), and the discovery that LCMV can cause long-term immune dysfunction months after infection (125), among many other important discoveries.…”
Section: Lymphocytic Choriomeningitis Virus Reporter-expressing Systemsmentioning
confidence: 99%
“…These include the replacement of wild-type viral GPC or NP segments with eGFP (104,106,107,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124), teal fluorescent protein (125), mCherry (126,127), or ZsGreen (128)(129)(130). Not only do these reporters allow for assessment of viral replication in less time than is needed for traditional plaque assays, but also they have been a powerful tool in highthroughput screening approaches used to identify small-molecule antivirals (131), identification of receptors required for host cell infection (126), and the discovery that LCMV can cause long-term immune dysfunction months after infection (125), among many other important discoveries.…”
Section: Lymphocytic Choriomeningitis Virus Reporter-expressing Systemsmentioning
confidence: 99%
“…LASV/vRNP cells were maintained in DMEM 10% FBS, 100 μg/ml zeocin, 10 μg/ml Bls, 100 mg/ml streptomycin, and 100 U/ ml penicillin. The recombinant (r)LCMV expressing GFP (rLCMV/GFP-P2A-NP, refer to as rLCMV/GFP) (Miranda et al, 2018), ZsGreen (ZsG) (rLCMV/ZsG-P2A-NP, refer to as rLCMV/ZsG) , and a single cycle infectious rLCMV expressing ZsG (rLCMVΔGPC/ZsG-P2A-NP, refer to as rLCMVΔGPC/ZsG) have been described.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The L RNA encodes the viral RNA dependent RNA polymerase (L polymerase), and the matrix Z protein. Advances in mammarenavirus molecular genetics have opened new approaches for the development of screening strategies to identify inhibitors of mammarenavirus multiplication Emonet et al, 2011a;Miranda et al, 2018;Welch et al, 2016). However, the use of these approaches with live LASV are complicated by the requirement of biosafety level 4 (BSL4) containment.…”
Section: Introductionmentioning
confidence: 99%
“…Lethal viral mutagenesis has also been identified as a possible mechanism for viral control (403, 404). While few studies have found drugs that target arenaviral NPs, one recent paper has identified a compound from a pyridine library that can reduce LCMV titers post-cell entry and is thought to affect NP and Z by unknown mechanisms (405).…”
Section: Development Of Vaccines For and Antivirals Against Arenavirumentioning
confidence: 99%